2020
DOI: 10.29390/cjrt-2020-019
|View full text |Cite
|
Sign up to set email alerts
|

Helmet CPAP revisited in COVID-19 pneumonia: A case series

Abstract: Introduction: Noninvasive positive pressure ventilation (NIPPV) plays an important role in the management of respiratory failure. However, since the emergence of the COVID-19 pandemic, utilization of traditional face mask NIPPV has been curtailed in part due to risk of aerosolization of respiratory particles and subsequent health care worker exposure. A randomized clinical trial in 2016 reported that an alternative interface, helmet NIPPV, may be more effective than traditional NIPPV at preventing intubation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…Among the possible dangers and limitations of the use of the snorkel mask, we find that the patient breathes the exhaled air again, which produces hypercapnia. To avoid this, flow rates (typically at least 50 L per minute) are needed to maintain adequate inspiratory positive airway pressure and expiratory positive airway pressure [ 10 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the possible dangers and limitations of the use of the snorkel mask, we find that the patient breathes the exhaled air again, which produces hypercapnia. To avoid this, flow rates (typically at least 50 L per minute) are needed to maintain adequate inspiratory positive airway pressure and expiratory positive airway pressure [ 10 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to commencing BiPAP, the patient must be assessed for a pneumothorax, ideally by a chest X-Ray or ultrasound. Due to the need for chest auscultation for COVID-19 patients, is not recommended as it increases the risk of transmission to the healthcare professional [8,111,112].…”
Section: Bilevel Positive Airway Pressure (Bipap)mentioning
confidence: 99%
“…The application of Positive End Expiratory Pressure (PEEP) assists in maintaining the patient's airway pressure prevents alveolar collapse, in turn increasing lung volumes and distends them to reduce the distance between the alveolar and the blood vessels to improve gaseous exchange. In severe COVID-19, initial CPAP setting have been suggested 10 cm H2O and 60% oxygen [14,110,112,[116][117][118][119][120][121][122].…”
Section: Continuous Positive Airway Pressure (Cpap)mentioning
confidence: 99%
“…[12] When treating COVID-19 affected patients, the use of helmets might bear the additional advantage of reducing virus environment contamination. [13,14] Recent reports suggest that helmet CPAP can be effective for COVID-19 treatment, [15][16][17] possibly combined with prone or lateral position. [18][19][20] In a multicenter cohort study Aliberti et al showed that helmet CPAP signi cantly increased PaO2/FiO2 from oxygen administration alone, but that treatment failure was frequent, occurring in 44% of patients who required intubation and invasive ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…days, with a PEEP of 10 [5-10] cmH 2 O and a FiO 2 of 50 [35-80]%. Such patients were discharged from hospital after 14[10][11][12][13][14][15][16][17][18][19] days. Patients requiring intubation (54, 31%) showed a higher heart rate on day one than those who did not (119, 68%) (92 [83-102] BPM vs. 80 [72-90], P<0.001).…”
mentioning
confidence: 99%